Should I Stay or Must I Go? Temporary Protection and Refugee Outcomes - Matilda Kilström; Birthe Larsen; Elisabet Olme (Copenhagen Business School (CBS), Department of Economics, 2018)
We study a Danish reform in 2002 that lowered the ex ante probability of refugees receiving permanent residency by prolonging the time period before they were eligible to apply for permanent residency. Assignment to the new rules was completely determined by the date of the asylum application and the reform was implemented retroactively. We formulate a simple search and matching model to derive predictions that can be tested using our data. Then we study the effects on educational and labor market outcomes and find that the reform significantly increased enrollment in formal education, especially for females and low skilled individuals. In terms of employment and earnings, coefficients are in general negative but non-significant. Other outcomes of interest are also studied. The reform had a negative impact on criminal activity driven by a reduction among males. There are no effects on health outcomes and significant but relatively small negative effects on childbearing for females. The results do not seem to be driven by selection, since the reform had no significant effect on the share that stayed in Denmark in the long run.
hdl:10398/9650
Keywords: J15; J24; J61; K37; 330; refugees; human capital; immigration law